2008
DOI: 10.3389/neuro.01.003.2008
|View full text |Cite
|
Sign up to set email alerts
|

Can attractor network models account for the statistics of firing during persistent activity in prefrontal cortex?

Abstract: Persistent activity observed in neurophysiological experiments in monkeys is thought to be the neuronal correlate of working memory. Over the last decade, network modellers have strived to reproduce the main features of these experiments. In particular, attractor network models have been proposed in which there is a coexistence between a non-selective attractor state with low background activity with selective attractor states in which sub-groups of neurons fire at rates which are higher (but not much higher) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 46 publications
2
50
1
Order By: Relevance
“…Many neurons combined in a network with recurrent connections exhibit so-called attractor dynamics (Hopfield 1982;Barbieri and Brunel 2008) attributed mainly to the hippocampus (Rolls and Kesner 2006;Lansner 2009;Cutsuridis and Wennekers 2009). This means that different activity patterns (e.g., incomplete input patterns) lead to the same (complete) activity pattern or cell assembly that can be interpreted as a memory item.…”
Section: Physiological Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…Many neurons combined in a network with recurrent connections exhibit so-called attractor dynamics (Hopfield 1982;Barbieri and Brunel 2008) attributed mainly to the hippocampus (Rolls and Kesner 2006;Lansner 2009;Cutsuridis and Wennekers 2009). This means that different activity patterns (e.g., incomplete input patterns) lead to the same (complete) activity pattern or cell assembly that can be interpreted as a memory item.…”
Section: Physiological Mechanismmentioning
confidence: 99%
“…If these neural networks are stimulated by an input, then the complexity "stores" the input in the neural network's activity pattern for a certain duration. A similar approach are attractor networks (Barbieri and Brunel 2008), which, however, require a specific, biologically unconfirmed, signal to turn off working memory activity and previously stored knowledge. (3) Working memory-short-term plasticity (theoretical) Short-term plasticity is a physiological candidate for working memory in neuronal networks (Barak and Tsodyks 2007;Mongillo et al 2008).…”
Section: Links Between Time Scales Of Memory and Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it has been reported that in ODR tasks, the coefficient of variation of the interspike interval distribution is close to 1, and even Ͼ1 for many of the neurons (Compte et al, 2003). Previous modeling works have attempted to account for this irregularity (Brunel, 2000;van Vreeswijk and Sompolinsky, 2004;Renart et al, 2007;Roudi and Latham, 2007;Barbieri and Brunel, 2008). However, in all these models, unless parameters are tuned, the neurons fire much too regularly in memory states.…”
Section: Introductionmentioning
confidence: 99%
“…The above firing rate model had the advantage of being much more efficient than a spiking model, while Fisher information in spiking models (Seriès et al 2004) and rate models (Spiridon and Gerstner 2001) have been found to be qualitatively similar. Moreover, implementation of realistic variability across a wide range of firing rates is challenging in spiking models (for a review see e.g., Barbieri and Brunel 2008).…”
Section: Network Setupmentioning
confidence: 99%